Third-Degree Price Discrimination in Two-Sided Markets - Alexandre de Cornière; Andrea Mantovani; Shiva Shekhar (Center for Economic Studies and ifo Institute (CESifo), 2023)
We investigate the welfare effects of third-degree price discrimination by a two-sided platform that enables interaction between buyers and sellers. Sellers are heterogenous with respect to their per-interaction benefit, and, under price discrimination, the platform can condition its fee on sellers' type. In a model with linear demand on each side, we show that price discrimination: (i) increases participation on both sides; (ii) enhances total welfare; (iii) may result in a strict Pareto improvement, with both seller types being better-off than under uniform pricing. These results, which are in stark contrast to the traditional analysis of price discrimination, are driven by the existence of cross-group network effects. By improving the firm's ability to monetize seller participation, price discrimination induces the platform to attract more buyers, which then increases seller participation. The Pareto improvement result means that even those sellers who pay a higher price under discrimination can be better-off, due to the increased buyer participation.
Keywords: D42; D62; L11; L12; 330; two-sided markets; price discrimination; network effects